Aniline-based silane as a primer for corrosion inhibition of aluminium - Flamini, Daniel Omar (2012)
Hybrid films based on polyaniline and polysiloxane moieties were successfully deposited on commercial aluminium alloy using N-(3- trimethoxysilylpropyl)aniline (AnSi) as primer. The spectroscopic studies conducted on both the silane solution and the resulting films, jointly with several corrosion tests in NaCl, strongly support the protection performance of the hybrid films. The overall study demonstrates that typical silane-based treatments with principally barrier action can gain in active properties if the silane compound contains monomers of conducting polymers as a functional group.